A Study on application of non-profit marketing concepts to Korea's civil society organizations - Park, Byung Ok (KDI School, 2000)
This thesis examines how nonprofit marketing concepts can be applied to the Korean situation, and how Korean CSOs can learn from nonprofit marketing to improve their performance. The marketing concept can be applied to all sorts of exchange behaviors. Korean CSOs can gain many useful insights from nonprofit marketing concepts in order to improve the efficiency and effectiveness of their activities. Korean civil organizations have unique characteristics different from the serviceoriented NPOs or society-enlightening groups, which have been the main objects of previous studies of nonprofit marketing. It is also important to pay attention to the facts that they have been developed through very different historical process. Therefore Korean CSOs should understand their unique characteristics and develop marketing strategies and tools that fit the Korean situation. The application of nonprofit marketing will meet strong resistance from most existing CSOs. Korean activists have a negative perception of marketing, regarding it as a manipulative tool applicable only for profit-seeking enterprises. Serious debate related to the concepts of efficiency, customer-orientation, competition, and to some of the ethical issues will be raised. Additional studies on these problems will be needed in the future.
Thesis(Master) --KDI School:Master of Economics and Policy,2000